Hubungan Perilaku Safety Riding Pengendara Ojek Online Dengan Kejadian Kecelakaan Lalulintas Di Kota Manado - Bryanza Amak; Nancy S.H. Malonda; Paul A.T. Kawatu (Indonesian Journal of Public Health and Community Medicine, 2020)
Background: Traffic accident is an event on the highway unexpected and unintentional involving vehicles with or without other road users which resulted in human casualties or property losses. The factors that cause accidents, human factor, vehicle, and environment. Factors highest cause of accidents is the human factor (human error). Behavioral safety riding is a safe state while driving.safety riding or safe driving behavior has a definition that varies is how rider motorcycles can drive safely, follow the rules and regulations in force with the aim of ensuring the safety of motorists and other road users. The research aims to determine the correlation between safety riding with traffic accident. Method: This research used analytic survey with cross sectional study. Place of research in Manguni Rider Online Communities and Community The Team rider motorcycle exhaust line in the city of Manado, in the month of September to December 2019. The sample in this study amounted to 80 people. Research variables are independent variables: behavioral safety riding and the dependent variable: the incidence of traffic accidents. The instrument of this research using questionnaires measuring instrument to conduct safety riding questionnaires and interviews to the incidence of traffic accidents.Data analysis included univariate and bivariate analysis using chi-square test 5% (Î± = 0,05) in SPSS. Result: The results of the study behavioral relationships online motorcycle rider safety riding with the incidence of traffic accidents was obtained p value = 0,478 and or = 1.400. Thus there is no relationship of Conduct Safety Riding Online Motorcycle taxi riders with occurrence of Traffic Accident In the city of Manado.Conclusion: the conclusion of this research has no correlation between safety riding with traffic accident in Manado.